1992
DOI: 10.1016/0165-4608(92)90346-a
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities and oncogenesis in cat leukemias

Abstract: The normal diploid number in domestic cat is 38. All three cell lines had numerical chromosome abnormalities with modal numbers of 37, 38 (pseudodiploid), and 39 respectively. All three cell lines also had structural (marker) chromosome abnormalities that were consistent within cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Chromosomal instability and the resulting aneuploidy, like other types of genomic instability, is considered to be important for multistep tumorigenesis through the accumulation of alterations responsible for malignant phenotype [15,22,30]. Although a number of chromosomal abnormalities have been revealed in cat tumors [9,10,42], the centrosome amplification has yet to be explored.…”
mentioning
confidence: 99%
“…Chromosomal instability and the resulting aneuploidy, like other types of genomic instability, is considered to be important for multistep tumorigenesis through the accumulation of alterations responsible for malignant phenotype [15,22,30]. Although a number of chromosomal abnormalities have been revealed in cat tumors [9,10,42], the centrosome amplification has yet to be explored.…”
mentioning
confidence: 99%
“…In order to provide basic cytogenetic information on the FasL gene in the cat, we regionally assigned the feline FasL gene (TNFSF6) to chromosome F1q12 → q13 by fluorescence in situ hybridization. Interestingly, monosomy and deletion of feline chromosome F1 were observed in feline leukemia virus-positive and negative lymphomas (Gulino, 1992), and a large marker chromosome F1 was detected in a cat with fibrosarcoma (Mayr et al, 1996). Therefore the present data will help to investigate molecular pathogenesis of apoptosis-related diseases in cats and also to understand comparative cytogenetics.…”
Section: Rationale and Significancementioning
confidence: 96%
“…Chromosome abnormalities of 10q23 → q25 involving the FAS region were characteristically found at a relatively high frequency in patients with NHL (Speaks et al, 1992), and a recent molecular analysis of FAS in NHLs demonstrates that the somatic disruption of FAS may play an important role in the pathogenesis of some lymphomas and autoimmune diseases (Gronbaek et al, 1998). Interestingly in cats, monosomy of chromosome D2 in a FeLV-positive lymphoma (Gulino, 1992) and trisomy of the chromosome in a neurofibroma (Kalat et al, 1990) are observed from the cytogenetic point of view. Therefore, the detailed assignment in the present study will help to investigate molecular pathogenesis of apoptosis-related diseases in cats and also to further develop comparative cytogenetics.…”
Section: Rationale and Significancementioning
confidence: 99%